A Major Difference between Law and Faith, in Luke and his Traditions - Kilgallen, John J. 1934-2019 (2004)
Discusses the difference between Mosaic Law and Faith based on the Acts. Significance of the baptism of the Samaritans by Peter and John to the unity between Samaritan church and the established Jerusalem church and its Apostles; Role of Paul in the teachings that Jesus Christ could not be ignored and has the eternal role regarding salvation; Relationship of Jesus of Nazareth to the Holy Spirit prior to His baptismal event.
Keywords: Apocryphal Acts of the Apostles; Apostles; DOCTRINAL theology; FAITH (Christianity); Jesus Christ; Jewish Law